2015
DOI: 10.1039/c5cc04620c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights for the development of Li–O2battery materials: addressing Li2O2conductivity limitations and electrolyte and cathode instabilities

Abstract: The Li-air battery has received significant attention over the past decade given its high theoretical specific energy compared to competing energy storage technologies. Yet, numerous scientific challenges remain unsolved in the pursuit of attaining a battery with modest Coulombic efficiency and high capacity. In this Feature Article, we provide our current perspective on challenges facing the development of nonaqueous Li-O2 battery cathodes. We initially present a review on our understanding of electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 134 publications
(284 reference statements)
7
123
0
1
Order By: Relevance
“…The overall results of the project concord well with other recent reports to conclude that this technology, despite its important promises, is still far from commercialization [14,[28][29]. A number of critical issues and challenges need to find solutions before an application can be envisioned.…”
Section: A) B)supporting
confidence: 67%
“…The overall results of the project concord well with other recent reports to conclude that this technology, despite its important promises, is still far from commercialization [14,[28][29]. A number of critical issues and challenges need to find solutions before an application can be envisioned.…”
Section: A) B)supporting
confidence: 67%
“…[34] Nevertheless,t he enhanced solubility of LiO 2 may increase the presence of superoxide species,which negatively impacts the stability of the electrolyte and the cathode following mechanisms as discussed in Section 2. [73][74][75] This effect has not been experimentally studied in the literature.…”
Section: The Cathode Reaction Pathways Influenced By the Electrolytementioning
confidence: 99%
“…2,3,12,13,15 However, the Li 2 O 2 on the separator observed here offers an alternative viewpoint on a suitable direction for optimization of the Li-O 2 battery. Previous studies have shown that the morphology of the discharge product observed on the cathode surface changes…”
Section: •¹mentioning
confidence: 99%